Potential impacts of desiccant-based drying and hermetic storage on the value chain for onion seeds in Nepal. Issue 2 (4th June 2018) - Timsina, Krishna P.; Bradford, Kent J.; Dahal, Peetambar; Shivakoti, Ganesh P.; Kunusoth, Keshavulu; Van Asbrouck, Johan; Bajracharya, Jwala; Pandey, Indra Raj
Abstract : Purpose: The purpose of this paper is to analyze the potential returns to value chain actors from employing desiccant bead drying and hermetic storage technology. Design/methodology/approach: Information was collected from 175 different onion ( Allium cepa L.) seed value chain actors in Nepal. Four different business models for the introduction of new bead drying and hermetic storage technology were compared to current practices through use of partial budgeting. Findings: The increase in net income throughout the chain was quite similar in all four models, ranging from US$28.86 to 29.61 per kg of onion seed, making it difficult to say that any single model is best for all situations. However, there are differences in sharing of positive net income and negative net income for different actors in different models. Moreover, about US$5.85 million incremental return could be earned per year in Nepal from improved preservation of onion seed alone. Research limitations/implications: This research assesses how to introduce a new technology, the dry chain concept to maintain seed quality, into the existing marketplace. Originality/value: This paper focuses on the economics of a novel technology and compares different business models and scenarios.